Analisis Pavement Condition Index dan Implikasinya terhadap Kecepatan Kendaraan di Lingkungan Perkotaan (Studi Kasus: Jalan Galaxy II Kota Palangka Raya) - Priskila, Eunike; Robby; Sutan Parasian Silitonga (Jurnal Serambi Engineering, 2025)
Galaxy II Street, located in the Jekan Raya District, was chosen as the study site due to its representative condition regarding road infrastructure issues in Palangka Raya City, particularly its damaged pavement. This study utilized two types of data: primary data and secondary data. The road damage assessment was conducted using the Pavement Condition Index (PCI) method based on ASTM D6433-07 standards, while vehicle speed analysis was carried out using the spot speed method. The results showed that Galaxy II Street had an average PCI value of 37, which is categorized as very poor. The analysis of vehicle speed indicated a negative correlation between the level of road damage and vehicle speed. The lower the PCI value, the lower the recorded vehicle speed. These findings are consistent with previous studies, which state that pavement condition has a significant influence on driving behavior.